Integrating Physical and Molecular Insights on Immune Cell Migration. Issue 8 (August 2018) - Moreau, Hélène D.; Piel, Matthieu; Voituriez, Raphaël; Lennon-Duménil, Ana-Maria
Abstract : The function of most immune cells depends on their ability to migrate through complex microenvironments, either randomly to patrol for the presence of antigens or directionally to reach their next site of action. The actin cytoskeleton and its partners are key conductors of immune cell migration as they control the intrinsic migratory properties of leukocytes as well as their capacity to respond to cues present in their environment. In this review we focus on the latest discoveries regarding the role of the actomyosin cytoskeleton in optimizing immune cell migration in complex environments, with a special focus on recent insights provided by physical modeling. Highlights: Immune cells in vivo mostly use non-adherent confined migration. This type of migration relies on myosin II-dependent actin retrograde flow, which generates forward propulsion forces by friction with the environment rather than through specific receptor–ligand interactions. Alternation of fast and slow migration conducted by distinct actin subcellular pools is observed in many immune cells. Such an intermittent migration mode can optimize space exploration by immune cells. Immune cell migration is guided by a combination of chemical and physical environmental cues. The actin cytoskeleton contributes to the detection of and response to these cues, allowing immune cells to integrate them and navigate in complex environments.